Depression and disability: comparisons with common physical conditions in the Ibadan study of aging (2008)
Objectives: To compare the effects of depression and chronic physical conditions on disability in elderly persons. Setting: Yoruba-speaking areas of Nigeria. Design: Interviews. Participants: Community-dwelling persons aged 65 and older. Method: Face-to-face interviews were conducted with a representative sample of community-dwelling persons aged 65 and older (N= 2,152) in the Yoruba-speaking areas of Nigeria (representing ~22% of the national population). Major depressive disorder (MDD) was assessed using the World Health Organization Composite International Diagnostic Interview. Chronic pain and medical disorders were assessed using self-report. Disorder-specific disability was evaluated using the Sheehan Disability Scale (SDS). Results: MDD was highly comorbid with each of the medical conditions (odds ratio range 1.3–2.0). A higher proportion of persons with MDD (47.2%) were rated severely disabled globally than those with arthritis (20.6%), chronic spinal pain (24.2%), or high blood pressure (25.0%). Subjects with MDD were also more likely to be severely disabled in three of the four domains of the SDS. In pair-wise comparisons, persons with MDD had significantly higher levels of disability than those with any of the disorders, with differences in mean scores ranging between -3.74 and -27.50. Conclusion: To reduce the public health burden of depression, its prevention and treatment require more clinical and research attention than currently given by developing countries.